High-dose-rate brachytherapy in the treatment of skin Kaposi sarcoma - María Ángeles González Ruiz; Juan Quirós Rivero; Julia Luisa Muñoz García; Joaquín José Cabrera Rodríguez; Yesika Ríos Kavadoy; María Francisca Ropero Carmona; Almudena Corbacho Campos; Fernando García Urra; María Cristina Cruz Muñoz; Amanda Ruiz Herrero; Pedro Almendral Manzano (Journal of Contemporary Brachytherapy, 2017)
Purpose : The aim of the study is to review our experience in treatment of Kaposi sarcoma (KS) lesions with high-dose-rate (HDR) brachytherapy. Material and methods : We present five new KS lesions (three patients) that were treated in our hospital from May 2016 to February 2017 with HDR brachytherapy using Valencia applicators. The treatment was delivered in 5 Gy fractions over five sessions, on alternate days. Total dose of 25 Gy (EQD2 31.25 Gy) was delivered. All patients were male, Caucasian, without a history of HIV, organ transplantation, or current immunosuppressive therapy. The median age was 76 years. Results : All lesions (100%) were located in lower limbs (60% in the ankle, 20% in the leg, and 20% in the foot), and their development was progressive. No lesion was greater than 2 cm (range, 0.5-1.5 cm). With a median follow-up of 15 months, all patients had a complete response to the treatment, with no evidence of local recurrence or tumor progression. Most of the patients (80%) had no acute toxicity; only one patient developed erythema grade 2. Conclusions : HDR brachytherapy could be a good option of treatment for these types of lesions, especially in elderly patients, or when cosmetic results are not good after surgery. Brachytherapy with the Valencia applicator, using hypofractionated regimen provides excellent results in terms of cosmetic and local control, and furthermore, facilitates treatment compliance, which is very relevant in elderly patients. HDR brachytherapy offers a simple, safe, quick, and attractive non-surgical treatment option.